Practical Microsoft Office 2013 - Parsons, June Jamrich; Oja, Dan; Mulder, Donna (Practical series, 2015)
Provides instructions on the basics of the Microsoft Office 2013 suite. This book comes with a robust BookOnCD, which is a digital version of the textbook that brings the book to life with videos, animated diagrams, software tours, and assessment opportunities that can be graded and tracked